Analysis of difficulties in learning biology online during the covid-19 pandemic in high school - Puji Rizky Widyaningsih; Ervan Johan Wicaksana; Raissa Mataniari (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
The Covid-19 disease has appeared since 2019. The minister of Education and Culture of the Republic of Indonesia issued circular letter number 4 of 2020. The circular letter explains that the teaching and learning process is implemented through online learning. This study aims to determine the implementation of the learning process, learning difficulties, and the causes of students having difficulty learning biology online. This research uses a descriptive qualitative approach. The research subjects were class X MIA at one of the high schools in Jambi Province. Data collection techniques used was documentation, Google form questionnaires, and interviews. The validity test is done by member check. Data analysis techniques using data reduction, data presentation, and concluding. Learning difficulties experienced by students are learning resources that are still limited, the internet network is not good, some students do not have smartphones, often turning off the camera during Google meet, students feeling burdened with the assignments given, lack of time available, and not concentrating. The causes of learning difficulties are the lack of effort from students to find learning resources, limited networks, smartphones owned by students in bad condition, and a home environment that is not conducive.Abstrak Penyakit covid-19 muncul sejak tahun 2019. Menteri pendidikan dan kebudayaan republik Indonesia mengeluarkan surat edaran nomor 4 tahun 2020. Surat edaran tersebut menjelaskan bahwa pelaksanaan proses belajar mengajar dilaksanakan melalui pembelajaran daring. Tujuan dari penelitian ini yaitu untuk mengetahui pelaksanaan proses belajar, kesulitan belajar dan penyebab siswa mengalami kesulitan belajar biologi secara daring. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Subjek penelitian adalah siswa kelas X MIA dan guru biologi kelas X MIA di salah satu SMA yang ada di Provinsi Jambi. Teknik pengumpulan data yang digunakan adalah dokumentasi, kuesioner Google form dan wawancara. Uji validitas yang dilakukan dengan cara member check. Teknik analisis data menggunakan reduksi data, penyajian data dan penarikan kesimpulan. Kesulitan belajar yang dialami siswa adalah sumber belajar yang masih terbatas, jaringan internet yang kurang baik, terdapat siswa yang tidak memiliki smartphone, sering mematikan kamera saat dilakukan Google meet, siswa merasa terbebani dengan tugas yang diberikan, kurangnya waktu yang tersedia dan tidak berkonsentrasi. Penyebab kesulitan belajar adalah tidak ada usaha dari siswa untuk mencari sumber belajar, terbatasnya jaringan internet, smartphone yang dimiliki siswa dalam keadaan kurang baik, dan lingkungan rumah yang tidak kondusif.